Method Of Assessment The Annual Flow Of The Wadi In The North Of Algeria - Ladjel, M.; Mezentseva, O. (University of Eloued جامعة الوادي, 2016)
In arid and semiarid climatic conditions of Northern Algeria surface water resources are limited and irregular in time and space. The water resources of the ephemeral streams (Wadi) are associated with the precipitation and depend on the latitude and altitudinal zonation. Large catchments drained the whole total runoff, which is equal to the difference between precipitation and evaporation. Groundwater runoff of small and medium rivers is proportional to the catchment area; evaporation is influenced by local factors. This paper proposes a new approach to the analysis of the geographical distribution of runoff specifying the vertical and latitudinal zonation of flow and the influence of the basin morphology. The transition from the climatic runoff estimates to the river runoff estimates was made using the Climatic factor of module local runoff, which can be mapped.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: precipitation; climate runoff; river flow; evaporation; potential evaporation.